“Theological Epistemologies and the Poetry of the Everyday: Reflections on Captivities and Cages.” (Theological Kronos, 2022)
This article is the result of the reflective experience on some of the epistemological processes present in my walk of faith, which have been influenced by elements of everyday life, unnoticed or ignored for a long time, and the recognition of how these have played a fundamental role in my process of learning and consolidating my faith. The text constitutes the dialogue between four reflective proposals, which, in their interrelation, result in the possibility of recognizing, thinking and dreaming of new ways of thinking and doing Theology. The proposals contemplated here are the epistemology of Ivone Gebara, the theology of Rubem Alves, the anthropology of Marcela Lagarde, and the criticism of Marcela Althaus-Reid. The author’s dialogical process occurs within the framework of the doctoral course in Theology on the thought of Rubem Alves, a dialogue that allows not only to perceive some of the social dynamics that create captivity in which women find themselves immersed, but also recognize the importance of the everyday, in the process of creating new reflections that contribute to the liberation of the oppressive systems present in said dynamics.
Keywords: Theology; Experience; Daily; epistemologies; Dialogue